Commissural and monosynaptic inputs to medial vestibular nucleus GABAergic neurons in mice - Kong, Dedi; Kong, Lingxi; Liu, Chengwei; Wu, Qianru; Wang, Jing; Dai, Chunfu (Frontiers in Neurology, 2024)
Objective MVN GABAergic neurons is involved in the rebalance of commissural system contributing to alleviating acute peripheral vestibular dysfunction syndrome. This study aims to depict monosynaptic inputs to MVN GABAergic neurons. Methods The modified rabies virus-based retrogradation method combined with the VGAT-IRES-Cre mice was used in this study. Moreover, the commissural connections with MVN GABAergic neurons were analyzed. Results We identified 60 nuclei projecting to MVN GABAergic neurons primarily distributed in the cerebellum and the medulla. The uvula-nodulus, gigantocellular reticular nucleus, prepositus nucleus, intermediate reticular nucleus, and three other nuclei sent dense inputs to MVN GABAergic neurons. The medial (fastigial) cerebellar nucleus, dorsal paragigantocellular nucleus, lateral paragigantocellular nucleus and 10 other nuclei sent moderate inputs to MVN GABAergic neurons. Sparse inputs to MVN GABAergic neurons originated from the nucleus of the solitary tract, lateral reticular nucleus, pedunculopontine tegmental nucleus and 37 other nuclei. The MVN GABAergic neurons were regulated by the contralateral MVN, lateral vestibular nucleus, superior vestibular nucleus, and inferior vestibular nucleus. Conclusion Our study contributes to further understanding of the vestibular dysfunction in terms of neural circuits and search for new strategies to facilitate vestibular compensation.